The Effect of Fluoride-releasing Elastomeric Chains on Streptococcus mutans Levels in Saliva and Dental Plaque in Orthodontic Patients - Zohreh Hedayati; Samaneh Sadeghi; Hamid reza Pakshir; Abdollah Derakhshandeh (Islamic Dental Association of Iran, 2013)
Background and Aim: During fixed orthodontic treatments the absolute number and percentage of salivary Streptococcus mutans increase. This will cause increase of enamel demineralization and dental caries. The purpose of present study is to evaluate the effect of fluoride-releasing elastomeric chains in the streptococcus mutans levels in saliva and bacterial plaque .   Materials and Methods: In this randomized clinical trial sixty patients, who were under fixed-orthodontic appliance treatments were selected and randomly divided into two groups of 30 each. Conventional elastomeric chains were used in group 1. As for the second group fluoride-releasing elastomeric chains were utilized. Four samples of saliva collected on days 0, 7, 14 and 28, and two plaque samples were collected on the beginning and finishing days in both groups. The fluoride-releasing and conventional elastomeric chains were removed on day 28. All samples were then used for microbial culture to count the Streptococcus mutans colonies. The results were analyzed statistically with the repeated measures Analysis of Variance (ANOVA) and Student t-tests .   Results: The result of Streptococcus mutans (CFU) in saliva at each time point in the study showed no statistically significant difference between the two groups ( p≥0.301 ). Comparison of the effect of elastomeric chains on the Streptococcus mutans colonization in dental plaque and elastomeric chains surface, also did not show any statistically significant difference between the two groups ( p= 0.317and 0.803 respectively) .   Conclusion: There was no clinical evidence that fluoride-releasing elastomeric chains were effective in reducing the formation and colonization of Streptococcus mutans in saliva and dental plaque .